2007
DOI: 10.1634/theoncologist.12-6-654
|View full text |Cite
|
Sign up to set email alerts
|

Extended Resection for Pancreatic Adenocarcinoma

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Discuss the evidence in favor of and against the role of surgical resection in the management of pancreatic adenocarcinoma.2. Explain how the components of an extended pancreatectomy, including total pancreatectomy, extended lymph node dissection, and major intestinal arterial resection, do not improve survival above what is provided after pancreaticoduodenectomy and are associated with substantial morbidity.3. Discuss how portal/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 47 publications
0
35
0
7
Order By: Relevance
“…La DPC es la técnica quirúrgica de elección para el tratamiento radical de las neoplasias ubicadas en el duodeno, región periampular, confluente bilio-pancreático y cabeza del páncreas (1)(2)(3). Aunque su indicación por lo general es en patología maligna, también puede ser el tratamiento de elección para algunas enfermedades benignas como la pancreatitis crónica, la distrofia quística de la pared duodenal, etc.…”
Section: Resultados De La Duodeno-pancreatectomía Cefálica Convencionunclassified
See 1 more Smart Citation
“…La DPC es la técnica quirúrgica de elección para el tratamiento radical de las neoplasias ubicadas en el duodeno, región periampular, confluente bilio-pancreático y cabeza del páncreas (1)(2)(3). Aunque su indicación por lo general es en patología maligna, también puede ser el tratamiento de elección para algunas enfermedades benignas como la pancreatitis crónica, la distrofia quística de la pared duodenal, etc.…”
Section: Resultados De La Duodeno-pancreatectomía Cefálica Convencionunclassified
“…La tasa de fístula pancreática clínicamente relevante varía de un 10-30% de los casos según las series (9-11), si bien la tasa global puede ser de hasta un 50% de los casos (8,11). La tasa de complicaciones globales se cifra en un considerable 36 -50 % (2,7,8,12,13). Mientras que la mortalidad postoperatoria en centros de referencia varía entre un 1-8% (7-13), en hospitales comarcales no universitarios puede llegar a superar el 15 % (14).…”
Section: Resultados De La Duodeno-pancreatectomía Cefálica Convencionunclassified
“…To this end, more radical or "extended" surgical techniques have been established in the last decades, whereat "extended" in this context means a more aggressive marginal clearance [26][27][28] . This may include total duodenopancreatectomy, resection of the portal-mesenterical axis, and extended lymph node dissection.…”
Section: Extended Pancreatectomymentioning
confidence: 99%
“…Also, most studies reveal no survival benefi t and increased morbidity and mortality with total pancreatectomy over pancreaticoduodenectomy and distal pancreatectomy [11,12]. However, in rare situations including a soft pancreas with risk of a leak from pancreatoenterostomy, or if positive margins on sequential frozen sections are obtained while resection is carried out into the pancreatic tail, or if there are papillomatous changes or dysplasia throughout the pancreatic duct, or if a family history of multicentric disease exists total pancreatectomy should be considered [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that segmental venous resection and subsequent reconstruction is the ideal means of managing tumours adherent to the SMV and PV, and can achieve survival equivalent to any margin-negative pancreaticoduodenectomy [17]. It is worth noting that the effi cacy of arterial resection is much lesser than venous resection, and histologically confi rmed tumour infi ltration into the vascular tunica media is associated with no signifi cant benefi t in long-term survival [13,14].…”
Section: Introductionmentioning
confidence: 99%